Coping with uncertain future during crisis: fictional expectations of starting hoteliers. Issue 2 (3rd April 2021) - Erkuş, Hilal; Terhorst, Pieter
ABSTRACT: This study is about the expectations of the future of hoteliers in the tourism city of Antalya who intend to start a new firm during the recent (geo)political crisis in Turkey.  The starting point of our analysis is that capitalism is a dynamic open system that is full of creativity and novelties. That is why entrepreneurs who plan to invest face a radical uncertainty about the future and can neither make rational decisions nor form rational expectations. Instead, their decisions are based on fictional expectations (Beckert) as a motivational basis of action that are not only individually but also socially constructed by a variety of social factors that are never discussed both in tourism and resilience literature. By doing a case study, the fictional expectations of starting hoteliers are explored. The main results are the fictional expectations of hoteliers are formed in interaction with other actors in the tourism industry and banks, and, notwithstanding the geopolitical crisis that severely hit tourism and future threats such as overtourism and pandemic, the hoteliers are optimistic about the future because of believing their luxury service of their (4 and 5) star hotels and the place quality of Antalya, Turkey.